2015
DOI: 10.1155/2015/962046
|View full text |Cite
|
Sign up to set email alerts
|

Urine Monocyte Chemoattractant Protein-1 and Lupus Nephritis Disease Activity: Preliminary Report of a Prospective Longitudinal Study

Abstract: Objective. This longitudinal study aimed to determine the urine monocyte chemoattractant protein-1 (uMCP-1) levels in patients with biopsy-proven lupus nephritis (LN) at various stages of renal disease activity and to compare them to current standard markers. Methods. Patients with LN—active or inactive—had their uMCP-1 levels and standard disease activity markers measured at baseline and 2 and 4 months. Urinary parameters, renal function test, serological markers, and renal SLE disease activity index-2K (rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…This denoting that most of the patients enrolled in the study are active proliferative LN cases. (Alharazy et al, 2015) found that there were significant differences between the active and inactive LN groups with regard to renal SLEDAI.…”
Section: Discussionmentioning
confidence: 87%
“…This denoting that most of the patients enrolled in the study are active proliferative LN cases. (Alharazy et al, 2015) found that there were significant differences between the active and inactive LN groups with regard to renal SLEDAI.…”
Section: Discussionmentioning
confidence: 87%
“…In LN, there is also evidence of higher levels of MCP-1 in active disease, with levels declining following immunosuppression and rising several months before a relapse. 12,[20][21][22] In each of the GN we studied, previous studies have shown urinary TGF-b1 levels to be elevated during active disease and to correlate with histologic characteristics and proteinuria. 15,[54][55][56][57] In patients with MN, higher initial urinary TGF-b1 levels were associated with a persistent nephrotic syndrome and kidney function decline at 12 months.…”
Section: Discussionmentioning
confidence: 94%
“…Urine MCP-1 was related with renal function and lupus disease activity. [ 15 ] Protein microarray is the high-throughput analysis approach for urine cytokine. We previously constructed protein microarray for detection of inflammatory cytokines and found differential expression of cytokines in CKD patients.…”
Section: U Rine C Ontains R mentioning
confidence: 99%